Preliminary psychometric validation of the multidimensional inventory of sport excellence: Anxiety and hardness scales - Sindik, J.; Schuster, S.; Botica, A.; Fiskus, M. (Croatian Sports Medicine Journal, 2015)
Sports psychologist needs to understand how psychological factors affect the performance of an individual, and must take account of individual differences among athletes. Although there are numerous psychological measurement instruments for assessing the important psychological characteristics of the athletes, it is important to select instruments to customize athletes with whom we work, adjusting with the work style of sports psychologists, as well as to available time and other constraints. The aim of this study is to determine the basic psychometric characteristics of three questionnaires, made out in the preliminary version of its own battery of questionnaires, called Multidimensional questionnaire sporting excellence (MUSI). Items cover space of following psychological characteristi cs: somatic and cognitive anxiety and mental hardiness / toughness. In this part of the study, participants were stratified only by gender. Our sample included 248 participants, of which 103 athletes (age 24.52 ± 11.80 years) and 145 female athletes (age 16.61 ± 6.69 years), in the Croatian sports clubs, competing in 16 different sports (archery, football, handball, bocce, bowling, cycling, karate, rowing, tennis, volleyball, basketball, synchronized swimming, triathlon, table tennis, chess, badminton). Results of factor analysis and examination of reliability of internal consistency showed that each of subscales in the battery MUSI has satisfactory reliability and validity, giving positive guidance for future adaptation of the questionnaires in MUSI for specific subpopulations of the athletes.